The Role of Village Government in the Development of Tourism Villages in Tempos Village, Gerung District, West Lombok Regency - Mar’atus Sholihah; Siti Ahdina Saadatirrohmi (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: The purpose of this study is to describe the role of the village government in developing a tourism village in Tempos Village and to identify the village government's impediments to developing a tourism village. Method: The descriptive qualitative research method was used. Techniques for gathering data include observation, interviews, and documentation. Checking the validity of the data using extended observations, increased persistence, and source triangulation. Results: According to the findings of this study, the Tempos Village government played four types of roles in the context of developing a tourism village. First, as an entrepreneur, I acquired land for a culinary tourism destination and set up sales stalls. Second, tourism development planning should be coordinated with tourism awareness groups (Pokdarwis). Third, providing assistance and budgeting funds for annual operational costs of 30 million rupiah. Finally, invite investors to participate. Contribution: This research can serve as a resource for various stakeholders interested in understanding the role of the Tempos Village government in developing village potential through the development of village-based tourist objects and attractions.